2017
DOI: 10.3390/v9050115
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Proteomic Analysis of Chitosan Oligosaccharide-Treated Rice Infected with Southern Rice Black-Streaked Dwarf Virus

Abstract: Southern rice black-streaked dwarf virus (SRBSDV) has spread from thesouth of China to the north of Vietnam in the past few years and severelyinfluenced rice production. Its long incubation period and early symptoms are not evident; thus, controlling it is difficult. Chitosan oligosaccharide (COS) is a green plant immunomodulator. Early studies showed that preventing and controlling SRBSDV have a certain effect and reduce disease infection rate, but its underlying controlling and preventing mechanism is unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…In rice, cross-talk between the responses to H 2 O 2 treatment and to RBSDV infection suggested pivotal roles of H 2 O 2 in the responses to RBSDV infection [ 17 ]. Recently, a label-free quantitative proteomic analysis showed that chitosan oligosaccharide enhanced the resistance of rice to RBSDV infection by activating the mitogen-activated protein kinase signaling cascade pathway [ 18 ]. To investigate the responses of maize seedlings to RBSDV infection at the proteome level, comparative proteomic analysis was performed.…”
Section: Introductionmentioning
confidence: 99%
“…In rice, cross-talk between the responses to H 2 O 2 treatment and to RBSDV infection suggested pivotal roles of H 2 O 2 in the responses to RBSDV infection [ 17 ]. Recently, a label-free quantitative proteomic analysis showed that chitosan oligosaccharide enhanced the resistance of rice to RBSDV infection by activating the mitogen-activated protein kinase signaling cascade pathway [ 18 ]. To investigate the responses of maize seedlings to RBSDV infection at the proteome level, comparative proteomic analysis was performed.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of total protein was calculated according to the Bradford method . The protein was digested with trypsin using the reported methods, and the enzymatic hydrolysate was dried for 6 h in a vacuum drier, and the dry residue was used for LC–MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the concentration of total protein was determined using the Bradford method [ 49 ]. Before the LC-MS/MS analysis, protein was digested with trypsin using reported methods [ 50 ].…”
Section: Methodsmentioning
confidence: 99%